Hadith #4096 - Sunan al-Nasa'i - al-Qasim bin Zakaria bin Dinar القاسم بن زكريا بن دينار القرشي; Matruf bin Tarayf al-Harithi مطرف بن طريف; Sa'id bin 'Amr bin Sahl al-Kundi سعيد بن عمرو بن سهل الكندي الأشعثي (Sunan al-Nasa'i)
The Messenger of Allah said: “Whoever is killed defending his wealth and is killed unjustly, Paradise will be his.”
Grade:

Hadith #4812 - Sunan al-Nasa'i - al-Qasim bin Zakaria bin Dinar القاسم بن زكريا بن دينار القرشي; Ayoub al-Sakhtiyani أيوب السختياني; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; ibn Abbas; Ikrama عكرمة; Sa'id bin 'Amr bin Sahl al-Kundi سعيد بن عمرو بن سهل الكندي الأشعثي; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan al-Nasa'i)
“The Messenger of Allah ruled that the Diyah for accidental killing is twenty Bint Makhad, twenty Bin Makhad, twenty Bint Labur, twenty Jadh’ah, and twenty Hiqqah.”
Grade: